Cadangan Karbon di atas Permukaan Tanah pada Kawasan Cagar Alam Maninjau Blok Rehabilitasi Silayang-Malabur, Kabupaten Agam - Novia Sherina A. Lubis; Irma Leilani Eka Putri (Jurnal Serambi Biologi, 2023)
The Maninjau Nature Reserve is a conservation forest area located in the Agam district and Padang Pariaman district. In this case the Silayang-Malabur block is included in the rehabilitation block where this block has been damaged both naturally and due to human actions such as illegal logging, conversion of forests to fields and so on which has an impact on reducing carbon stocks. Therefore, it is necessary to do research in calculating carbon stocks to determine carbon stocks. This research was carried out in the Maninjau Nature Reserve area, Silayang-Malabur Rehabilitation Block, Agam Regency, which was conducted from December 2022 - January 2023. This type of research was descriptive research by collecting data on the level of trees, poles, saplings, and seedlings. Data collection used purposive random sampling which was divided into 2 research areas, namely natural forest and open/damaged forest. The sample plots used were a single plot of 3 plots randomly distributed in each study area. Biomass estimation using allometric equations. Based on the results of research on carbon stocks stored above ground level in the Maninjau Nature Reserve area of the Silayang-Malabur Rehabilitation Block, Agam Regency of 148,415 ton C/ha in natural forest areas and 34,397 ton C/ha in open/degraded forest area with a total carbon stock of 182,812 ton C/ha.